Preparation method of graded porous carbon material for negative electrode of potassium ion battery

By preparing graded porous carbon materials, using carbon thermal reduction reaction and heteroatom doping technology, the problem of insufficient rate performance and structural reversibility of potassium ion batteries is solved, and the high-performance potassium storage specific capacity, cycle stability and rate performance is improved, which is suitable for the industrialization process of large-scale energy storage systems.

CN119750543APending Publication Date: 2025-04-04NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411957786.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Potassium ion batteries face the problem of insufficient rate performance and structural reversibility in large-scale energy storage systems, especially the volume deformation caused by the large ion radius of K+, which affects the structural integrity of the battery and the realization of high power density.

Method used

By thoroughly mixing the recovered polymer material with a pyrolysis auxiliary agent, the graphite layer is layered, loosened and increased the layer spacing, and combined with heteroatom doping, a graded porous carbon material is prepared. The material improves the conductivity and active sites through phosphorus doping treatment, and ultimately shows excellent potassium storage capacity, cycle stability and rate magnification performance.

Benefits of technology

It realizes the high-performance potassium storage specific capacity, cycle stability and rate performance of the negative electrode material of potassium ion battery, and is suitable for the industrialization of large-scale energy storage systems, while reducing production costs and toxic gas emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750543A_ABST
    Figure CN119750543A_ABST
Patent Text Reader

Abstract

The invention relates to the field of porous carbon materials, and provides a preparation method of a graded porous carbon material for a negative electrode of a potassium ion battery, which comprises the following steps: fully mixing a recycled polymer material with a pyrolysis auxiliary agent, and pressing the mixture into a precursor with a required target shape; heating the precursor to 1000 DEG C or above in a protective atmosphere, and pyrolyzing to obtain a three-dimensional porous carbon material with a precursor shape; and further mixing the obtained carbon material with phosphoric acid, heating to an annealing temperature in protective gas, preserving heat, and naturally cooling to obtain the phosphorus-doped graded porous carbon material negative electrode. According to the preparation method, the pyrolysis auxiliary agent is adopted, zinc steam generated by carbon thermal reduction reaction in the pyrolysis process enables a graphite layer to be layered and loosened, interlayer spacing is increased, and in combination with the effects of interlayer spacing increase, conductivity improvement and the like brought by heteroatom doping, the finally obtained carbon material shows excellent potassium storage specific capacity, cycling stability and rate capability; the negative electrode material is suitable for large-scale energy storage of potassium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of porous carbon materials, and in particular to a method for preparing a graded porous carbon material for a negative electrode of a potassium ion battery. Background Art

[0002] The widespread use and insufficient recycling of plastics not only accelerates the unsustainable consumption of fossil fuels, but also further drives the demand for renewable energy and large-scale energy storage equipment. However, renewable energy sources such as wind, solar, hydropower and tidal power are difficult to achieve real-time and continuous power supply due to their inherent intermittent and unstable characteristics. Therefore, the development of large-scale energy storage equipment with low cost and long life has become an important strategy to overcome the limitations of renewable energy. Among the existing large-scale energy storage technologies, rechargeable batteries have become the most suitable choice due to their cost-effectiveness, scalability, safety, energy conversion efficiency and flexible installation methods. However, due to the limited lithium resources, lithium-ion batteries are difficult to meet the expanding grid-scale energy storage needs in the future.

[0003] Over-reliance on lithium resources has triggered concerns about the sustainability of lithium and transition metals, and has promoted the development of non-lithium energy storage technologies. This has become an important direction of global energy research and has played a key role in shaping future energy storage systems. Among the many alternative technologies, potassium-ion batteries have gradually attracted widespread attention due to their significant chemical and economic advantages and are regarded as one of the potential alternatives for large-scale energy storage systems.

[0004] The advantages of potassium ion batteries are reflected in the following three aspects:

[0005] 1) Cost advantage: The abundance of potassium in the earth's crust and its compatibility with low-cost aluminum foil as the negative electrode current collector enable potassium-ion batteries to avoid the thermodynamic formation problem of aluminum-potassium intermetallic compounds during manufacturing.

[0006] 2) Wide voltage range: In carbonate electrolytes, KK + The lower standard electrode potential reduces the negative electrode cutoff voltage and avoids the deposition of metallic potassium, thereby supporting operation over a wider voltage range, which distinguishes potassium-ion batteries from lithium-ion batteries and sodium-ion batteries.

[0007] 3) High power density: Potassium ions have a small Stokes radius and a fast diffusion rate in the electrolyte, which provides good conditions for achieving high power density, making potassium ion batteries a strong competitor in large-scale energy storage systems.

[0008] For large-scale energy storage systems for power grids, superior rate performance and cycle stability remain core challenges. + and Na + In comparison, K + The large ionic radius of K limits the rate performance and structural reversibility. + The large size leads to significant volume deformation (volume expansion of up to 61% in potassium-ion batteries, compared to only 10% in lithium-ion batteries). Therefore, the development of high-performance anode materials to ensure that potassium-ion batteries maintain structural integrity during the electrochemical process while achieving high power density and practical low-cost large-scale production is the key to solving this problem.

[0009] Among various negative electrode materials, carbon materials have become the most promising negative electrode candidates due to their low cost, high conductivity, wide availability and structural flexibility. However, the potassium storage capacity of standard graphite materials is poor, and it is urgent to develop a new preparation process to obtain high-performance porous carbon negative electrode materials for potassium ion batteries. Summary of the invention

[0010] The present invention provides a method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery. The recovered polymer material is fully mixed with a pyrolysis auxiliary agent and then pyrolyzed. Zinc vapor generated by a carbon thermal reduction reaction during the pyrolysis causes the graphite layer to be stratified and loosened and increases the interlayer spacing. Combined with the effects of increased interlayer spacing and improved electrical conductivity brought about by heteroatom doping, the finally obtained carbon material exhibits excellent potassium storage specific capacity, cycle stability and rate performance, and is suitable as a negative electrode material for potassium ion batteries for large-scale energy storage.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] A method for preparing a graded porous carbon material for a potassium ion battery negative electrode comprises the following steps: fully mixing a recovered polymer material with a pyrolysis auxiliary agent, and pressing the mixture into a precursor of a desired target shape; heating the precursor to above 1000°C in a protective atmosphere, and pyrolyzing to obtain a three-dimensional porous carbon material having the shape of the precursor; further mixing the obtained carbon material with phosphoric acid, and heating to 800°C in a protective atmosphere and annealing for 2 hours, and naturally cooling to obtain a phosphorus-doped graded porous carbon material negative electrode.

[0013] Preferably, the recycled polymer material is selected from one or more of polyacrylonitrile-polybutadiene-polystyrene (ABS), polyethylene, polypropylene, polybutadiene, polyisoprene and dynamic chemical cross-linking modified products thereof.

[0014] Preferably, the pyrolysis auxiliary agent is selected from one or more of zinc oxide, zinc carbonate and zinc nitrate.

[0015] Preferably, the protective atmosphere is selected from one or more of nitrogen, argon and helium.

[0016] Preferably, the mass ratio of the recovered polymer material to the pyrolysis auxiliary agent is (0.4-1.2):1.

[0017] Preferably, the mass ratio of the carbon material to the phosphoric acid in the phosphating treatment is (0.05-0.5):1.

[0018] Preferably, the phosphating annealing temperature is 500-900° C., and the holding time is 0.2-5 h.

[0019] The growth mechanism and chemical evolution process of carbon materials are as follows:

[0020] Below 200°C: free water and unreacted monomers are volatilized;

[0021] 200-350℃: The cross-linked structure of the cross-linked polymer is carbonized. The cross-linked structure introduces steric hindrance, which hinders the expansion of the grains and the degree of graphitization at subsequent high temperatures, thereby increasing the distance between graphite layers;

[0022] 350-500℃: The main mass loss stage, including dehydrogenation and main chain polycondensation. The introduction of zinc oxide greatly inhibits the formation of cyano compounds, ammonia and benzene derivatives, thereby reducing the emission of toxic gases. In addition, zinc oxide promotes the transition of the polymer from the molten state to the solid carbonization, inhibiting the rearrangement of the aromatic fragments;

[0023] 500-1000℃: Elimination of heteroatoms. Zinc oxide is reduced to zinc vapor through carbon thermal reduction, which relaxes the graphite interlayer structure and increases the graphite interlayer spacing, which is beneficial to improving the cycle stability and rate performance of potassium storage;

[0024] Above 1000℃: deep carbonization and graphitization stage.

[0025] The porous carbon block electrode prepared by the present invention is microscopically composed of a partially disordered phosphorus-doped nanographite structure, and forms a micron-sized thin layer structure prepared by reduction of a zinc oxide carbon source, providing potassium storage active sites for electrochemical reactions; the thin layer structures are connected to each other to form open carbon microsphere units, providing channels for material transmission; the carbon microsphere units constitute a macroscopic carbon material block, and the continuous block structure is conducive to the transmission of electrons and phonons, thereby forming a hierarchical porous structure.

[0026] The beneficial effects of the present invention are:

[0027] (1) This study provides a low-cost and efficient solution for plastic recycling and upgrading, which not only helps improve the plastic circular economy, but also provides important support for the development of energy storage. Through this strategy, plastic waste can be converted into advanced carbon materials, providing new ideas for addressing resource shortages and environmental pollution, and promoting the transition to a sustainable future of circular economy and renewable energy.

[0028] (2) Using zinc oxide, zinc carbonate, zinc nitrate, etc. as carbonization aids, high-performance carbon materials with hierarchical porous structures were obtained through carbothermal reduction reaction and zinc evaporation, while avoiding the template etching and pickling steps during high-temperature pyrolysis and reducing toxic gas emissions. In addition, zinc oxide can be further regenerated through oxidation reactions during pyrolysis, thereby reducing costs.

[0029] (3) Phosphorus doping increases the conductivity and active sites of porous carbon materials. The introduction of large-sized phosphorus atoms also increases the spacing between graphite layers, thereby improving the specific capacity, cycle stability and rate performance of porous carbon materials for potassium storage, which is beneficial to the industrialization process of potassium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the preparation process of the graded porous carbon negative electrode material prepared in Example 1.

[0031] Figure 2 This is a scanning electron microscope image of the prepared hierarchical porous carbon material negative electrode.

[0032] Figure 3 This is the X-ray diffraction pattern of the prepared hierarchical porous carbon material negative electrode.

[0033] Figure 4 The rate performance of potassium storage of the prepared hierarchical porous carbon material negative electrode.

[0034] Figure 5 The cycling performance of the prepared hierarchical porous carbon material negative electrode for potassium storage at a current density of 5A / g. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below through specific embodiments.

[0036] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0037] Example 1

[0038] A method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery, such as Figure 1 As shown, the following steps are included:

[0039] Step 1. Take 5g of the recovered dynamically cross-linked polyacrylonitrile-polybutadiene-polystyrene copolymer resin and 9g of zinc oxide powder, heat to 170°C in an internal mixer, and mix until the solid color is evenly distributed and then press into round flakes;

[0040] Step 2. The solid obtained in step 1 is heated from room temperature to 1100° C. at 3° C. / min in an argon atmosphere and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a three-dimensional porous carbon material having the shape of the precursor;

[0041] Step 3. The carbon material obtained in step 2 is further mixed with phosphoric acid in a mass ratio of 1:10, and heated from room temperature to 800°C at 3°C / min in an argon atmosphere and annealed for 2h. After natural cooling, a phosphorus-doped graded porous carbon material can be obtained.

[0042] Figure 2 This is a scanning electron microscope image of the phosphorus-doped hierarchical porous carbon material negative electrode prepared in Example 1. The thin layer yarn-like structure will increase the specific surface area, increase the active sites of the electrochemical reaction, and shorten the K + diffusion path and ease K + The stress and volume expansion after insertion help improve the rate performance of potassium ion batteries; the open carbon microsphere structure helps the electrolyte to penetrate into the carbon microspheres quickly and ensures that K + There is sufficient contact between the inner surface of the porous carbon; the disordered graphite carbon layers in the macroscopically connected bulk structure are beneficial to improving the potassium storage capacity, while the ordered graphite layers are beneficial to improving the conductivity.

[0043] Figure 3 This is the X-ray diffraction pattern of the phosphorus-doped graded porous carbon material negative electrode prepared in Example 1. Phosphorus doping increases the interlayer spacing of the graphite layer. According to the Bragg law, the (002) peak at 24.29° corresponds to a graphite interlayer spacing of 0.365 nm.

[0044] Figure 4 The rate performance of potassium storage of the phosphorus-doped graded porous carbon material negative electrode prepared in Example 1. At different current densities of 0.1, 0.2, 0.5, 1, 2, 5 and 10 A / g, the corresponding specific capacities are 454, 452, 428, 381, 330, 258 and 209 mAh / g, respectively.

[0045] Figure 5 The cycle performance of potassium storage at a current density of 5A / g of the phosphorus-doped graded porous carbon material negative electrode prepared in Example 1. After 10,000 cycles, the capacity is still maintained at 192mAh / g, and the coulombic efficiency is as high as 99.9%, showing excellent cycle stability and large-scale energy storage prospects.

[0046] Comparative Example 1

[0047] A method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery comprises the following steps:

[0048] Step 1. Take 5g of the recovered dynamically cross-linked polyacrylonitrile-polybutadiene-polystyrene copolymer resin and 9g of zinc oxide powder, heat to 170°C in an internal mixer, and mix until the solid color is evenly distributed and then press into round flakes;

[0049] Step 2. The solid obtained in step 1 is heated from room temperature to 1100° C. at 3° C. / min in an argon atmosphere and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a three-dimensional porous carbon material having the shape of the precursor;

[0050] Compared with Example 1, Comparative Example 1 is different in that the phosphating step is omitted. Figure 2 It is shown that the morphology of the carbon material obtained in Comparative Example 1 is similar to that of the phosphorus-doped graded porous carbon material in Example 1. Figure 3 The X-ray diffraction spectrum shows that the (002) peak corresponds to a graphite interlayer spacing of 0.357 nm, which is smaller than the phosphorus-doped graded porous carbon material in Example 1, and the cycle specific capacity and rate performance are also slightly worse.

[0051] Comparative Example 2

[0052] A method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery comprises the following steps:

[0053] Step 1. Take 5g of the recycled polyacrylonitrile-polybutadiene-polystyrene copolymer resin and 9g of zinc oxide powder, heat to 170°C in an internal mixer, and mix until the solid color is evenly distributed and then press into round flakes;

[0054] Step 2. The solid obtained in step 1 is heated from room temperature to 1100° C. at 3° C. / min in an argon atmosphere and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a three-dimensional porous carbon material having the shape of the precursor;

[0055] Compared with Example 1 and Comparative Example 1, Comparative Example 2 differs in that non-crosslinked polyacrylonitrile-polybutadiene-polystyrene copolymer resin is used. Figure 2 It is shown that the morphology of the carbon material obtained in Comparative Example 2 is similar to that of the phosphorus-doped graded porous carbon material in Example 1, but the layered structure is thicker, which is not conducive to stress release after potassium insertion. Figure 3 The X-ray diffraction pattern shows that the (002) peak corresponds to a graphite interlayer spacing of 0.345 nm, which is smaller than the interlayer spacing of the porous carbon materials in Example 1 and Comparative Example 1, and the cycle specific capacity and rate performance are correspondingly worse.

[0056] Comparative Example 3

[0057] A method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery comprises the following steps:

[0058] Step 1. Take 5 g of the recovered polyacrylonitrile-polybutadiene-polystyrene copolymer resin and press it into a round sheet;

[0059] Step 2. The solid obtained in step 1 is heated from room temperature to 1100° C. at 3° C. / min in an argon atmosphere and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a carbon material;

[0060] Compared with Example 1, Comparative Example 1 and Comparative Example 2, Comparative Example 3 is different in that uncrosslinked polyacrylonitrile-polybutadiene-polystyrene copolymer resin is used, and the pyrolysis auxiliary agent zinc oxide is not added. Figure 2 The morphology of the carbon material obtained in Comparative Example 3 is different from the porous carbon materials in Example 1, Comparative Example 1 and Comparative Example 2, showing a dense block structure with fewer pores, which is not conducive to potassium storage. Figure 3 The X-ray diffraction pattern shows that the (002) peak corresponds to a graphite interlayer spacing of 0.342 nm, which is smaller than the porous carbon materials in Example 1, Comparative Example 1 and Comparative Example 2, and the rate performance is also the worst.

[0061] The above embodiments and comparative examples illustrate that chemical crosslinking, zinc oxide-assisted pyrolysis and phosphorus doping treatment all have an important influence on improving the potassium storage performance of the hierarchical porous carbon material, and the omission of any step will lead to a decrease in the potassium storage performance of the carbon material.

[0062] After the above pyrolysis auxiliary agents are changed to zinc carbonate and zinc nitrate, the above preparation steps and potassium storage performance maintain similar characteristics. This is because zinc carbonate and zinc nitrate will also decompose into zinc oxide during the pyrolysis process, and the released gas is conducive to the formation of a porous structure, thus helping to improve the potassium storage performance of the porous carbon material.

Claims

1. A method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery, characterized in that: The following steps are involved: The recovered polymer material is fully mixed with a pyrolysis auxiliary agent, and the mixture is pressed into a precursor of a desired target shape; the precursor is heated to above 1000°C in a protective atmosphere, and pyrolyzed to obtain a three-dimensional porous carbon material; the obtained carbon material is further mixed with phosphoric acid, and the temperature is raised to an annealing temperature in a protective gas and kept warm, and after natural cooling, a phosphorus-doped graded porous carbon material negative electrode is obtained.

2. The method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery according to claim 1, characterized in that: The recycled polymer material is selected from one or more of polyacrylonitrile-polybutadiene-polystyrene (ABS), polyethylene, polypropylene, polybutadiene, polyisoprene and dynamic chemical cross-linking modified products thereof.

3. The method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery according to claim 1, characterized in that: The pyrolysis auxiliary agent is selected from one or more of zinc oxide, zinc carbonate and zinc nitrate.

4. The method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery according to claim 1, characterized in that: The protective atmosphere is selected from one or more of nitrogen, argon and helium.

5. The method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery according to claim 1, characterized in that: The mass ratio of the recovered polymer material to the pyrolysis auxiliary agent is (0.4-1.2):

1.

6. The method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery according to claim 1, characterized in that: The mass ratio of the carbon material to the phosphoric acid in the phosphating treatment is (0.05-0.5):

1.

7. The method for preparing a hierarchical porous carbon material for a negative electrode of a potassium ion battery according to claim 1, characterized in that: The phosphating annealing temperature is 500-900℃, and the holding time is 0.2-5h.